2014
DOI: 10.1186/1476-511x-13-191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spirulina platensis supplementation on lipid profile in HIV–infected antiretroviral naïve patients in Yaounde - Cameroon: a randomized trial study

Abstract: BackgroundCardiovascular diseases (CVD) and metabolic alterations are among the majors public health concern that have been reported in people living with HIV infections. Factors contributing to cardio metabolic syndrome in HIV include body fat distribution, dyslipidemia, insulin resistance, cardiovascular dysfunction and inflammation. The aim of the study was to determine the effect of Spirulina platensis (Cyanobacteriaceae) supplementation versus local diet on lipid profile in HIV-infected antiretroviral-nai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Lipid concentrations were all improved in ischemic heart disease patients with hypercholesterolemia, whereas no effects on any of the lipid parameters were seen in obese subjects [15]. In HIV patients [12] and hypertensive subjects [41], TC and LDL-C concentrations decreased and those of HDL-C increased. In elderly, only TC concentrations were decreased [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid concentrations were all improved in ischemic heart disease patients with hypercholesterolemia, whereas no effects on any of the lipid parameters were seen in obese subjects [15]. In HIV patients [12] and hypertensive subjects [41], TC and LDL-C concentrations decreased and those of HDL-C increased. In elderly, only TC concentrations were decreased [42].…”
Section: Discussionmentioning
confidence: 99%
“…Spirulina (Arthrospira platensis or maxima), belonging to the family of cyanobacteria, is a microalga containing high amounts of proteins, vitamins and light-harvesting structures such as C-phycocyanin [7]. Animal [8,9] and several-but not all-human trials [10][11][12][13][14][15] have suggested that spirulina lowers serum total cholesterol (TC) and / or LDL-C concentrations. Studies in rats have now suggested that inhibition of intestinal cholesterol absorption could be the mechanism underlying the LDL-C reduction [9].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of spirulina supplements in human studies has been reported. This varied from 1 g/day (Mazokopakis, Starakis, Papadomanolaki, Mavroeidi, & Ganotakis, ), up to 10 g/day (Ngo‐Matip et al, ) with various physiopathological states and different durations of administration. The daily dose of Si supplied in the present study was 0.57 mg/kg, which represents 40 mg of Si for un adulte of 70 kg which could considered as nutritional supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, there is little work on the combined effects of ART and nutraceuticals. In Cameroon, Ngo Matip et al showed that the daily consumption of 10 g of spirulina powder for 6 months would stimulate the proliferation of CD4 while decreasing the viral load in ART-naive PLHIV [11,12]. However, there are no data on the effect of Spirulina platensis on the oxidative, inflammatory and immunological status of Cameroonian patients, carriers of HIV-1 in adjunction with ART.…”
Section: Introductionmentioning
confidence: 99%